DETERMINING OF THE EQUIVALENT AND OPTIMUM DIAMETERS OF CONE-CYLINDER TIP WITH SOIL BROACHING SPURS - Kravets, S. V.; Posmitjukha, O. P.; Suponyev, V. M. (Science and Transport Progress, 2017)
Purpose. Building of new railway tracks and facilities, repair and replacement of existent underground utilities and communications is related to the receipt of horizontal cavities in soil by trenchless method. A static soil broaching with a working body with cone tip is the most widespread method in practice of forming a pilot hole at the trenchless laying of distributive communications. However, in the process of implementation of project calculations, receipt of pilot hole and subsequent expansion to the necessary sizes, there is a question of workings effort calculation methods. Existent methods are based on empiric dependences and experimental coefficients which diminish exactness of calculations and increase the cost of works. Methodology. The work proposes the dependence for determination of equivalent diameter of cone tip depending on the hole diameter and theoretical method for calculation of optimum parameters of soil broaching head using the well-known parameters: type of soil and its humidity, that determined by the State Construction Regulations (DBN). Findings. The results of the theoretical studies can be used to increase the efficiency of the working equipment for soil broaching by static method during trenchless laying of underground utilities and communications. Originality. The authors establish the dependence of the equivalent diameter of the cone base on the diameter of the cylindrical part of the broaching head, which allows for removal of the frictional force from the static broaching on the lateral cylindrical surface of the tip. Practical value. The obtained theoretical calculations for determining the optimal diameters of the cone tip with soil broaching spurs made it possible to establish that if thediameteroftheconeisgreaterthanthemaximumdiameterofthehole (soilcavity), thenthefrontalresistanceofthecone-cylindertipincreasesmoreintensivelythantheresistanceofthecylindricalpartofthetip. The maximum reduction in the broaching force takes place for a soil cavity whose diameter is 2 times smaller than the maximum limit diameter. When conducting the calculations regarding the choice of the size of working bodies for soil broaching, the source data include the type of soil, and its characteristics by DBN, as well as the moisture content of the soil determined by traditional methods.